Konstitusi Ekonomi Syariah di Indonesia (Melacak Argumen Konstitusi terhadap Penerapan Ekonomi Syariah) - Syaugi Syaugi (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2017)
As a constitution, the Indonesian Constitution of 1945 regulates how the national economic system should be arranged and developed. In the perspective of the constitution, the implementation of the sharia economy does not mean the state directs a particular economic ideology. Philosophically, the ideals of Indonesian economic law is to initiate and prepare the legal concept of economic life. Shariah economy has a strong foundation both formally shariah and formal constitution. Formally shariah means the existence of shariah economy has a strong foundation in the Indonesian legal system. Formally constitution means, in the context of the state, the Shariah economy has a constitutional basis. The existence of laws relating to shariah economy shows that the Indonesian economic system gives a place to the shariah economy.